2018
DOI: 10.3906/biy-1707-36
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic contents of Teucrium polium L. and Teucrium scordium L. associated with their protective effects against MMC-induced chromosomal damage in cultured human peripheral blood lymphocytes

Abstract: Teucrium species have been used in traditional medicine for treatment of different diseases. The aim of this study was to investigate polyphenolic contents by high-performance liquid chromatography (HPLC), and the genotoxic effect of methanolic extracts of Teucrium polium and Teucrium scordium using the cytokinesis-block micronucleus (CBMN) assay on human peripheral blood lymphocytes (PBLs) from healthy donors. The HPLC analysis showed that extracts consist of phenolic acid (gallic, vanillic, caffeic, chloroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…For cancer therapy, to determine the potential anticancer effects of T. polium, all these in vitro studies showed the essentiality of the animal experimentation and clinical trials. T. polium contains five phenolic acids and six flavonoids, the most important therapeutic polyphenolic compounds [9,31]. In our study, moderate and high concentrations of plant extractions showed a protective effect for many genotoxicity tests.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…For cancer therapy, to determine the potential anticancer effects of T. polium, all these in vitro studies showed the essentiality of the animal experimentation and clinical trials. T. polium contains five phenolic acids and six flavonoids, the most important therapeutic polyphenolic compounds [9,31]. In our study, moderate and high concentrations of plant extractions showed a protective effect for many genotoxicity tests.…”
Section: Discussionsupporting
confidence: 51%
“…Quercetin-3-O-β-D-glucuronopyranoside (QGC) that has anti-oxidative, antitumor and anti-inflammatory effects in vivo, the most important flavonoid glucoside extracted from Teucrium and Rumex species [7,9,28,29]. The antimutagenic and anticancerogenic effects of T. polium were tested in the mammalian system and this plant extract was reported to decrease the SCE and chromosomal abnormalities [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decoction and infusion of the aerial parts of T. polium were analyzed by LC-MS/MS and luteolin-glycosides, pelargonin, and fumaric acid were exhibited as main constituents [ 48 ]. Twelve phenolic compounds were detected in the methanol extract of T. polium , containing high levels of catechin, luteolin, apigenin, rutin, quercetin, and chlorogenic acid whereas in the methanolic extracts of T. scordium five phenolic compounds were identified such as catechin, rutin, vanillic and p -coumaric acids [ 49 ]. In another study, the polyphenolic profiles of four Teucrium species from Macedonia were investigated and one hydroxycinnamic acid, eight phenylethanoid glycosides, flavonoid aglycones, and glycosides were found in the extract [ 47 ].…”
Section: Resultsmentioning
confidence: 99%